Increasing the odds for high-performance teams : lessons learned - Leholm, Arlen G. (Michigan State University Press, 2006)
"Increasing the Odds for High-Performance Teams - Lessons Learned is intended to assist professionals in private, public, and not-for-profit organizations who want to use teams to enhance job performance. Also, it is intended to be helpful to the team members, team leaders, mentors, coaches, and administrators across these sectors who want to diagnose their team and organizational conditions, in order to make improvements."--Jacket